Cardiovascular Effects of Stimulators of Soluble Guanylate Cyclase Administration: A Meta-analysis of Randomized Controlled Trials - Stamerra, Cosimo Andrea; Di Giosia, Paolo; Giorgini, Paolo; Jamialahmadi, Tannaz; Sahebkar, Amirhossein (Current atherosclerosis reports, 2024)
Purpose of review Heart failure (HF) is one of the main causes of cardiovascular mortality in the western world. Despite great advances in treatment, recurrence and mortality rates remain high. Soluble guanylate cyclase is an enzyme which, by producing cGMP, is responsible for the effects of vasodilation, reduction of cardiac pre- and after-load and, therefore, the improvement of myocardial performance. Thus, a new therapeutic strategy is represented by the stimulators of soluble guanylate cyclase (sGCs). The aim of this meta-analysis was to analyze the effects deriving from the administration of sGCs, in subjects affected by HF. A systematic literature search of Medline, SCOPUS, and Google Scholar was conducted up to December 2022 to identify RCTs assessing the cardiovascular effects, as NT-pro-BNP values and ejection fraction (EF), and all-cause mortality, of the sGCs. Quantitative data synthesis was performed using a random-effects model, with weighted mean difference (WMD) and 95% confidence interval (CI) as summary statistics. Recent findings The results obtained documented a statistically significant improvement in NT-proBNP values (SMD: − 0.258; 95% CI: − 0.398, − 0.118; p < 0.001) and EF (WMD: 0.948; 95% CI: 0.485, 1.411; p < 0.001) in subjects treated with sGCs; however, no significant change was found in the all-cause mortality rate (RR 0.96; 95% CI 0.868 to 1.072; I2, p = 0). Summary The sGCs represent a valid therapeutic option in subjects suffering from HF, leading to an improvement in cardiac performance.